A COMPARATIVE STUDY BETWEEN EXTROVERT AND INTROVERT STUDENTS ON THEIR SPEAKING SKILL IN THE ELEVENTH GRADE AT SMKN KABUH - Zuan Istigfaroh (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
This study is an attempt to discover about the extrovert and introvert students’ speaking skill in eleventh grade at State Vocational High School Kabuh. The participants were from P, Q, and R class. The samples of  this research were 63 students. The design of the research was comparative analysis design.  The data were obtained through questionnaire of personality whether the students are introvert or extrovert after that the researcher given speaking test for students. To analyze the data’s of questionnaire of extrovert and introvert students and speaking score. SPSS 20 were used. According the finding, there were 50 introvert students and 13 extrovert students. The mean of extrovert students speaking skill is 72.6 while the mean of introvert students speaking skill is 75.2. To measure students’ speaking ability, the researcher needs to interpret the output in the “Independent T-test”. Based on the output, it is known that the significant value Levene’s Test for Equality of Variances is 0.984 > 0.00 so it can be analyze that the variant data of extrovert and introvert is homogeny or same. While, the significant value (2-tailed) it is 0.175 > 0.05. Therefore Ho (Zero Hypothesis) was accepted and Ha (Alternative Hypothesis) was rejected.